A Case Study of Corporate Facilitated Community Based Tourism Development at Ide Sorowako Beach - Masriana Masriana; Masour Shqiarat; Nuttapong Jotikasthira (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to analyze the mechanisms of corporate-community collaboration in CBT development. It specifically seeks to answer: